Blockchain as a frontier in biotechnology and bioenergy applications. Issue 3 (March 2022) - Loy, Adrian Chun Minh; Lim, Juin Yau; How, Bing Shen; Yoo, Chang Kyoo
Abstract : The fourth Industrial Revolution is stimulating a fast-paced and resilient industrial internet of things (IIoT) ecosystem. Blockchain, a decentralized digital ledger technology, plays a crucial role in improvising, securing, and streamlining traditional biotechnology-related industrial processes with IoT and creates a sustainable nexus between social, economic, and environmental aspects.